Kiai and Political Relations Reconciling Politics and Religion in Indonesia - Mohammad Hidayaturrahman; Sudarman Sudarman (AL-TAHRIR, 2018)
Abstract : This research was conducted to reveal the relationship between kiai and politics in its journey in Indonesia. Also, it explores whether the relationship that occurred to be a pattern of religious and political reconciliation. Therefore, it is obvious that the kiai's interaction as a religious figure which holds political power has a principal meaning in bringing peace. Furthermore, it find out whether the kiai's involvement in politics solely for the sake of power itself, or for the benefit of the ummah and humanity. This research collected data by in-depth interviews with kiai who became head of the region, and political observers from universities, also supported by the search of existing literature either online or offline. The findings showed that there are at least five relationship models identified. Furthermore, the relationship became one of the media for the establishment of political harmony which is considered dirty and full of intrigue with religion. Finally, it is suggested that more specific research is required on what factors influencing to be the conservation of political and religious harmony in Indonesia, thus, the involvement of religious leaders/kiai in politics never leads to conflict.الملخص :جري هذا البحث العلمي لجلاء علاقة خاصة بين العلماء و السياسية في إندونيسيا منذ إستقلال هذا البلاد حتى الأن. تبعا لهذ, تستفاد هذا البحث لإلمام نوع هذه العلاقة, أهي كإحدى الوسائل في اتحاد بين الدين و السياسية كالأسس الحياة الوطنية في إندونسيا. و لعلّ بهذا البحث ظهر مباني العلاقة علماء إندونيسيا بقواد السياسية (على قصد قوة السياسية كان أم فردية, أو غيره) في تحصيل إتحاد الجماعة والإجتماعية معنا حقيقيا. جمع هذا البحث البيانات المتنوعة مما يتعلق بهذا البحث و ملاحظة وقيعية. و بجانب ذالك جمع البيانات من كتب و رسائل العلمية بما يتعلق به. و في تفسير البيانات جاء بمقابلات عميقة بالأفراد الذي يعتبر كالعلماء أو القواد السياسي أو المراقب في مجال السياسي. وأما نتيجة لهذا البحث هو هناك خمسة علاقة  مهمة التي تأثرت به الموازنة في حياة الإجتماعية أو السياسية في إندونيسيا.Abstrak: Penelitian ini dilakukan untuk mengetahui relasi yang terjadi antara kiai dan politik dalam perjalanannya dari waktu ke waktu di Indonesia. Hal ini sekaligus untuk mendalami apakah relasi yang terjadi menjadi salah satu pola mendamaikan agama dan politik. Sehingga dengan begitu akan menjadi lebih jelas interaksi kiai sebagai tokoh agama dengan kekuasaan politik, memiliki makna penting dalam perdamaian. Apakah keterlibatan kiai dalam politik semata-mata untuk kepentingan kekuasaan itu sendiri, atau karena kepentingan umat dan kemanusiaan. Penelitian ini mengumpulkan data dengan wawancara mendalam (indeph interview) dengan kiai yang menjadi kepala daerah, dan pengamat politik dari perguruan tinggi, juga ditopang dengan penelusuran literatur yang ada baik yang bersifat daring maupun luring.. Dari penelitian yang dilakukan, ditemukan beragam relasi politik dan kiai yang terjadi di Indonesia. Sedikitnya ada lima model relasi yang berhasil diidentifikasi dalam kajian ini. Selanjutnya relasi tersebut menjadi salah satu katalisator bagi terjalinnya harmoni politik yang selama dianggap kotor dan penuh intrik dengan agama yang dianggap suci. Diperlukan penelitian lebih spesifik mengenai faktor apa saja yang akan terus menjadi kelestarian harmoni politik dan agama di Indonesia, sehingga keterlibatan tokoh agama, kiai dalam politik tidak pernah berujung pada konflik.